WITH XR TECHNOLOGIES, NEXT TREND IN THE WORLD OF WORK: WILL BE AVATARS AND DIGITAL TWINS - Tiziana Primavera (mediaGEO soc. coop., 2021)
The article critically investigates the possibilities offered by new interactive visual technologies for remote professional collaboration, highlighting the legal aspects yet to be defined.